Pre-Adipocyte Determination and Adipocyte Differentiation of Stromal Vascular Cells Isolated From Intramuscular Tissue of Hanwoo Beef Cattle Treated by Acetate and Propionate - T. G. Wandita; N. Joshi; H. H. Kim; S. J. An; S. G. Hwang (Faculty of Animal Science, Bogor Agricultural University, 2018)
The effects of acetate and propionate in enhancing intramuscular fat (marbling) deposition in beef cattle are poorly understood. This study aimed to evaluate the effects of acetate and propionate on pre-adipocyte determination and adipocyte differentiation in stromal vascular cells (SVC) isolated from the intramuscular tissue of Hanwoo beef cattle. SVC were isolated and treated with different concentrations of acetate and propionate (0.125 to 1 mM). Pre-adipocyte determination was observed through the Zfp423 (Zinc finger protein 423) and Pref-1 (Pre-adipocyte factor-1) genes expressions, which were important transcription factors used to identify committed pre-adipocytes. Adipocyte differentiation was determined based on the lipid accumulation, triglyceride contents, and their molecular activities related to adipogenic markers. The results suggest that acetate supports pre-adipocyte determination in SVC which is observed to increase the expression of Zfp423 and Pref-1 along with the increasing acetate concentration. Propionate treatment was seen to significantly affect lipid accumulation as well as triglyceride content in SVC, compared to acetate treatment. Furthermore, propionate treatment very significantly increased the expressions of PPARγ, C/EBPα, SREBP-1c, and FABP4. In conclusion, acetate likely enhances pre-adipocyte determination, while propionate effectively promotes adipogenesis in SVC isolated from the intramuscular tissue of Hanwoo beef cattle.